Structuring Polysemy in English Learners' Dictionaries: A Prototype Theory-Based Model. (24th September 2018) - Lu, Huaguo; Wei, Xiangqing
Abstract: Prototype Theory provides new insights into the structure of polysemy. In order to apply these insights, researchers recommend that logical sense ordering be used to represent the polysemic structure in English learners' dictionaries. However, our examination of entries quoted from MEDAL2 reveals that logical sense ordering and its enhanced versions encounter difficulties in structuring polysemy: they can neither do justice to the multidimensional structure of polysemy nor clarify how one sense extends to another. We propose drawing a semantic graph as a supplement to the linearly-structured entry, enhancing the graph with sense link illustrations modeled on the COBUILD defining style, and presenting both the graph and the illustrations in a customizable way.